A Study On Relation Between Accounting Treatment For Capitalization Of R&D Expenditure And Earnings Management In The Korean Defense Industry - Im, Kyungkook; Im, Chaechang (Journal of Applied Business Research, 2018)
Overall, this paper examines and finds the relation between the ratio of accounting treatment for capitalization of research and development expenditure (RCR&D). The theoretical model derived from panel analysis resource on Korean defense industry information from 2009 to 2014 indicates that the RCR&D positively affect earnings management direction through a significantly positive relationship. Also, the effect of large defense industry firms’ RCR&D on earnings management direction is higher than that of small ones despite that large defense industry firms have discretionary accruals in (-) direction compared with small ones. In addition, the effect of defense industry firms’ RCR&D on earnings management direction is strong especially in earnings increasing group. Also the change of RCR&D is positive influence on discretionary accruals. This enforces that RCR&D can be related with earnings management direction.